Direct Oral Anticoagulants in Frail Older Adults: A Geriatric Perspective - Ho, Prahlad; Brooy, Beth La; Hayes, Lachlan; Lim, Wen Kwang (Seminars in Thrombosis and Hemostasis, 2015)
Direct oral anticoagulants (DOACs) have changed the paradigm of anticoagulation management, improving patient convenience as well as possibly reducing the incidence of spontaneous intracranial hemorrhage. However, concerns remain with these agents because of the lack of monitoring capacity and availability of readily accessible specific antidotes. This is particularly pertinent in the older population, specifically the frail older adults who have multiple comorbidities, higher risk of falls, and increased bleeding risk. This group has not been specifically studied in the DOAC randomized controlled trials and, hence, extrapolation of these data into this population should be done cautiously. We provide a review of the use of DOACs in the older frail population from both hematological and geriatric perspectives, as well as propose an algorithm for how these agents may be used in this frail population.
Keywords: direct oral anticoagulants; older adults; frailty; bleeding